FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIR MENJADI AKUNTAN PUBLIK - Rusdiansyah, Yunifan; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to analyze some factors which give influence to the student interest to become public accountant which consist of work market, professional training, payroll, professional recognition, social value, work environment, and personality. This research has been conducted at STIESIA and PERBANAS. The sample collection of this research has been done by using purposive sampling with the criteria allaccounting students in seventh semester. The source of data of this research has been obtainedby conducting research to the 100 accounting students by issuing questionnaires directly. The analysis method has been carried out by using multiple linear regressions. The result of this research shows that: (1) The professional training does not have any influence to the career selection to become a public accountant. (2) Payroll has positive influence to the career selection to become a public accountant. (3) The professional recognition has positive influence to the career selection to become a public accountant. (4) Social value does not have any influence to the career selection to become a public accountant. (5) Environment does not have any influence to the career selection to become public accountant. (6) Personality has positive influence to the career selection to become a public accountant.Keywords: professional training, payroll, professional recognition, career selection to become a public accountant.